Phyllosphere bacterial community and metabolomic analysis revealed the mechanism of Cd tolerance in the bryophyte Tortella tortuosa (Hedw.) Limpr - Zhu, Yongqi; Li, Qiuge; Feng, Lanlan; Dong, Yijie; Zhang, Yuanpei; Nurmaimaiti, Nigati; Mamut, Reyim (Frontiers in Plant Science, 2024)
Phytoremediation is a safe and green technology for the remediation of heavy metal pollution, a global environmental problem. Bryophytes are well known for their special physiological properties, but there is little research on the use of bryophytes for phytoremediation. In this indoor experiment, the impacts of 40 days of Cd pollution (1 (T1), 5 (T2), 10 (T3) mg•L -1 ) on Cd absorption, growth and physiological characteristics, and phyllosphere bacterial diversity of Tortella tortuosa were explored. The results showed that the maximum Cd absorption capacity of T. tortuosa was 5.0135 mg•kg -1 . The contents of leaf chlorophyll a (Chl a) and chlorophyll b (Chl b) in T. tortuosa decreased (p < 0.05) with the increase of Cd concentration. Especially, the Chl a and Chl b contents of the T3 treatment reduced by 88% and 91%, respectively compared with those of the CK (0 mg Cd L -1 ). The catalase (CAT) and peroxidase (POD) activities of the T3 treatment reduced by 55% and 85%, respectively (p < 0.05), and the malondialdehyde (MDA) content increased by 167%, compared with those of the CK. Under Cd exposure, Cyanobacteria (63.49%) and Proteobacteria (26.62%) were the dominant bacterial phyla. The highly abundant phyllosphere bacteria were negatively correlated with the Cd concentration, antioxidant enzyme activity, and chlorophyll content in T. tortuosa, and positively correlated with the relative abundances of Neomycin and N-Acetyl-L-Glutamic acid.Although the severe Cd pollution could affect the physiological and metabolic characteristics of T. tortuosa, T. tortuosa had a strong absorption capacity for Cd. Therefore, it could be used for phytoremediation of heavy metal pollution. This study will provide a reference for the remediation of soil heavy metal pollution.